Convergence in the Structure of Foreign Trade - Theoretical Approaches and Challenges for Bulgaria - Pirimova, Vera (Research Papers, 2020)
The report summarized a set of theoretical approaches to analyzing the convergence of foreign trade and its structural components. Three groups of applied models and empirical studies of convergence in the structure of foreign trade are classified. Based on the interpretation and analysis of models belonging to the three groups, the alternative character, the specific analytical capabilities and the applicability of the examined models are revealed and proved. There are some challenges for Bulgaria in the context of the effects and commodity structure of Bulgarian exports, which can be taken into account in analyzes of the structural convergence of country's foreign trade with that of other EU countries.
Keywords: Theoretical approaches; Foreign trade; Foreign trade structure; Convergence